Analisis Target Market dan Marketing Mix 4p dalam Meningkatkan Volume Penjualan Restoran HongKongBay, Gading Serpong - Nelvina Ruth; Jennie Calosa; Sherlen Frelinsia Goh; Vivian Wijaya; Dyah Cahyasari (Yayasan Literasi Sains Indonesia, 2023)
This research is research regarding increasing sales volume based on the target market and 4P marketing mix at the Hong Kong Bay restaurant, Gading Serpong. The target market and 4P marketing mix implemented by Hong Kong Bay restaurants are in accordance with the target market. However, there are still several shortcomings in the 4P marketing mix because this restaurant is a new restaurant that opened at the end of 2022. The aim of the research is to analyze the target market and 4P marketing mix in increasing the sales volume of the Hong Kong Bay restaurant. This research was conducted using descriptive qualitative methods, with the data collection process carried out through interviews, observation and documentations. The results of this research indicate that the implementation of the 4P target market and marketing mix in Hong Kong Bay restaurants has not been implemented optimally and is still in the development stage and increasing sales volume.